Pharmacy Students' Attitudes and Perceptions of "Virtual Worlds" as an Instructional Tool for Clinical Pharmacy Teaching - Claire Englund; Maria Gustafsson; Gisselle Gallego (MDPI AG, 2017)
The objectives of this study were to explore pharmacy students' perceptions and experiences of three-dimensional virtual worlds (3DVWs) as an instructional tool for clinical pharmacy teaching. Semi-structured interviews were carried out with Master of Science in Pharmacy students who had participated in communicative exercises in a 3DVW. Interviews were digitally recorded, transcribed and analyzed using thematic analysis. More than half of the students were positive to using 3DVWs for educational purposes and see the advantages of having a setting where communication can be practiced in an authentic but 'safe' environment available online. However, many students also reported technical difficulties in using the 3DVW which impacted negatively on the learning experience. Perceived ease of use and usefulness of 3DVWs appears to play an important role for students. The students' level of engagement relates to not only their computer skills, but also to the value they place on 3DVWs as an instructional tool.